Location Problems in Transportation Networks - Peter Czimmermann (Communications - Scientific letters of the University of Zilina, 2016)
It is known that many optimisation problems on networks are NP-hard. However, it seems that the real transport networks have some interesting properties which allow us to find a „good“ solution in reasonable time. In this paper, we suggest and study some new parameters of the transportation networks which could be useful in optimisation problems. We define the evenness and the robustness of the solution. We also concern ourselves with the statistical distribution of distances and edge values in transportation networks.